The cutting of ultrathin sections with the thickness less than 20 nm from biological specimens embedded in resin blocks - Nebesářová, Jana; Hozák, Pavel; Frank, Luděk; Štěpan, Petr; Vancová, Marie (Microscopy research and technique, 2016)
Low voltage electron microscopes working in transmission mode, like LVEM5 (Delong Instruments, Czech Republic) working at accelerating voltage 5 kV or scanning electron microscope working in transmission mode with accelerating voltage below 1 kV, require ultrathin sections with the thickness below 20 nm. Decreasing of the primary electron energy leads to enhancement of image contrast, which is especially useful in the case of biological samples composed of elements with low atomic numbers. As a result treatments with heavy metals, like post-fixation with osmium tetroxide or ultrathin section staining, can by omitted. The disadvantage is reduced penetration ability of incident electrons influencing the usable thickness of the specimen resulting in the need of ultrathin sections of under 20 nm thickness. In this study we want to answer basic questions concerning the cutting of extremely ultrathin sections: Is it possible routinely and reproducibly to cut extremely thin sections of biological specimens embedded in commonly used resins with contemporary ultramicrotome techniques and under what conditions? Microsc. Res. Tech. 79:512-517, 2016. © 2016 Wiley Periodicals, Inc.
Keywords: ultramicrotomy; Microscopy, Electron; Microtomy; epoxidové pryskyřice; design vybavení; elektronová mikroskopie; Mice; srdce; low voltage electron microscopy; Equipment Design; resin embedding; ultrathin sectioning; Polymers; myokard; zvířata; Myocardium; Epoxy Resins; Heart; myši; Plastic Embedding; polymery; zalévání tkání plastickou hmotou; mikrotomie; Animals